2005
DOI: 10.3354/meps291125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diatom nutrient limitation on copepod development: the role of essential lipids

Abstract: The development of 2 copepod species was studied with nutrient-limited algae as the sole food source. Thalassiosira weissflogii was grown under different levels of nitrogen and phosphorus limitation. Young copepodite stages of Temora longicornis (Müller) and Pseudocalanus elongatus (Boeck) developed at significantly reduced rates, both when fed with the nitrogen-and the phosphorus-limited diatom. At high levels of nutrient limitation, the copepods often did not reach maturity. The lipid composition of the diat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
95
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 59 publications
2
95
1
Order By: Relevance
“…Tonon et al (2002) also reported accumulation of DHA in T. pseudonana and P. lutheri, although the incorporation into TAGs was significantly lower and accumulation started later during the course of batch growth. In other studies, EPA or DHA content per algal biomass was reduced or not significantly affected by culture age or nutrient limitation (Klein Breteler et al 2005;Hsiao and Blanch 2006;Gong et al 2013;Nalder et al 2015).…”
Section: Introductionmentioning
confidence: 76%
“…Tonon et al (2002) also reported accumulation of DHA in T. pseudonana and P. lutheri, although the incorporation into TAGs was significantly lower and accumulation started later during the course of batch growth. In other studies, EPA or DHA content per algal biomass was reduced or not significantly affected by culture age or nutrient limitation (Klein Breteler et al 2005;Hsiao and Blanch 2006;Gong et al 2013;Nalder et al 2015).…”
Section: Introductionmentioning
confidence: 76%
“…FA composition of prey was shown to be involved in the extent of competition in predators and its seasonal succession (Klein Breteler et al, 2005;McMeans et al, 2015). However, although FA tracers were widely used in aquatic food webs from algae via zooplankton to fish, both in freshwater (e.g., Ahlgren et al, 1997;McMeans et al, 2015) and marine systems (Rossi et al, 2006), understanding of FAs transfer in food webs involving jellyfish is still poor.…”
Section: Introductionmentioning
confidence: 99%
“…Phytoplankton and other protists vary widely in their composition and nutritional content, causing the quality of copepod diets to vary significantly in the oceans (Jonasdottir et al 2005, Klein-Breteler et al 2005. Understanding the extent of natural variability in food quality is important because poor food quality can affect the growth, production and reproduction of copepods and fish (e.g.…”
Section: Introductionmentioning
confidence: 99%